Guia para condução de estudos em boca dividida em dentistica - Zanatta, Rayssa Ferreira [UNESP]; Silva, Tânia Mara da [UNESP]; Esper, Maria Ângela Lacerda Rangel [UNESP]; Bresciani, Eduardo [UNESP]; Caneppele, Taciana Marco Ferraz [UNESP]; Gonçalves, Sergio Eduardo de Paiva [UNESP] (Editora Cubo, 2017)
The split-mouth design used in some clinical trials make a randomization scheme on site level where two treatments are randomly assigned to sites of one of the two halves of the mouth. The aim of this review was to summarize guidelines for conducting split-mouth clinical studies in Restorative Dentistry. This is a review performed through scientific articles published between 2004 and 2014 indexed in MEDLINE, PubMed and Scielo databases. The study evaluated USPHS and FDI criteria. The current review showed the main characteristics used in splitmouth studies presented the Restorative Dentistry literature, as ethical aspects, sample calculation, methods of selection and evaluation patients, in order to provide a guideline for clinical conduction. It showed a standard of methodologies to enable comparison among studies.
Guidelines for conducting split-mouth clinical studies in restorative dentistry
Keywords: Clinical studies; Dentistry; Split-mouth design